Hippocampal subfields alterations in adolescents with post‐traumatic stress disorder. Issue 4 (27th October 2018) - Postel, Charlotte; Viard, Armelle; André, Claire; Guénolé, Fabian; de Flores, Robin; Baleyte, Jean‐Marc; Gerardin, Priscille; Eustache, Francis; Dayan, Jacques; Guillery‐Girard, Bérengère
Abstract: Reexperiencing symptoms in adolescent Post‐Traumatic Stress Disorder (PTSD) are characterized by the apparition of vivid intrusive images of the traumatic event. The emergence of these intrusions is thought to be related to a deficiency in context processing and could then be related to hippocampal alterations. The hippocampus is a complex structure which can be divided into several subfields, namely, the Cornu Ammonis (CA1, CA2, and CA3), the subiculum, and the dentate gyrus (DG). As each subfield presents different histological characteristics and functions, it appears more relevant to consider hippocampal subfields, instead of only assessing the whole hippocampus, to understand the neurobiology of PTSD. Hence, this study presents the first investigation of structural alterations within hippocampal subfields and their links to reexperiencing symptoms in adolescent PTSD. Hippocampal subfields were manually delineated on high‐resolution MRI images in 15 adolescents (13–18 years old) with PTSD and 24 age‐matched healthy controls. The volume of the region CA2‐3/DG region was significantly smaller in the PTSD group compared to controls in both hemispheres. No other significant difference was found for other subfields. Moreover, the volume of the left CA2‐3/DG was negatively correlated with the intrusion score (as measured by the Impact of Events Scale‐Revised) in the PTSD group. To conclude, an alteration in the hippocampal subregion CA2‐3/DG, known to resolve interferences between new and similar stored memories, could participate in the apparition of intrusive trauma memories in adolescents with PTSD.